A New Family Principle: The American Family Goes Transnational - Šesnić, Jelena (2010)
The essay examines possible imbrications of the description of the American family nowadays and the latest developments in new American studies, termed the transnational turn. The idea is to look at the notion of the family critically, to consider it always as an integral part of the national self-imagining, and thus, not surprisingly, entangled with some notions of American exceptionalism. However, as suggested primarily by feminist and gender criticism from the 1970s onwards, the work of domesticity and its companion term sentimentalism—always conveniently linked with the structures of gendering of American society and its institutions—ought to be seen as ideological modes and examined for their specific effects. This could be dramatized as the inversion of the family principle, where we see „standard“, normative families caught up in and trying to respond to the realities proceeding from the outside, whether that outside is placed within the domestic confines or internationally. Some of these include the adoption of foreign nationals, the inclusion of immigrants, threats by international terrorist networks (Muslim and radical leftist), economic changes wrought by globalization that shake up traditional communities, natural catastrophes, etc. These challenges are either psychological or, strictly speaking, social, but often enough they elicit and evoke a set of responses that are articulated in a series of contemporary US novels centering on the family, its dissolution or its reconstitution along different lines. The novels under consideration will include the following (the list is tentative): Jonathan Franzen, The 27th City and The Corrections ; Ann Tyler, Digging to America ; Jonathan Raban, Surveillance ; Richard Russo, Empire Falls and Claire Messud, Emperor's Children. The main line of the argument will go to show that it is necessary to consider the transnationalization of the US-American family as an important token of contemporary shifts in the definition of American exceptionalism, and as a way to reconsider the idea of transnationalism as one way of dealing with otherness, from its acknowledgment to its domestication. Arguably, the American domestic sphere and the family as its primary institution testifies in the changes it has undergone in the past decades also to some salient shifts in the collective ideological make-up of American society.
Projekt MZOS
Projekt MZOS
ENG